Around the tradition of the Wielkopolska table: objects, people, customs - Prałat, Emilian (Perspektywa stołu, 2023)
The article is devoted to presenting the table and dining room in the perspective of the material legacy related to the Wielkopolska landed gentry. Attention was paid to objects and places of historical importance, associated with figures important for the culture. There are also fragments of memoirs and correspondences devoted to, inter alia, tables at which spiritistic séances were held. Through the analysis of individual testimonies, attention was drawn to the multi-level importance of the table in the culture of the nineteenth and early twentieth centuries.